2004
DOI: 10.1097/00005131-200409000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of the Less Invasive Stabilization System, Angled Blade Plate, and Retrograde Intramedullary Nail for the Internal Fixation of Distal Femur Fractures

Abstract: All 3 fixation devices (LISS, ABP, and IMN) offer sufficient torsional stability and sufficient proximal fixation that withstands axial loading without failing. The LISS provides improved distal fixation, especially in osteoporotic bone, at the expense of more displacement at the fracture site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(152 citation statements)
references
References 22 publications
2
144
0
6
Order By: Relevance
“…Zlowodzki et al compared LCP, blade plates, and retrograde nailing in extra-articular fractures. 7 Strength under axial compression was better with the LCP system than with the blade plate or nailing, by 34 and 13% respectively, but strength under torsion was reduced. [8][9][10][11][12] The authors observed better distal fixation with the LCP system with loss of distal fixation in only one LCP plate (6%), three blade plates (38%) and eight losses with retrograde intramedullary nailing (100%).…”
Section: Discussionmentioning
confidence: 95%
“…Zlowodzki et al compared LCP, blade plates, and retrograde nailing in extra-articular fractures. 7 Strength under axial compression was better with the LCP system than with the blade plate or nailing, by 34 and 13% respectively, but strength under torsion was reduced. [8][9][10][11][12] The authors observed better distal fixation with the LCP system with loss of distal fixation in only one LCP plate (6%), three blade plates (38%) and eight losses with retrograde intramedullary nailing (100%).…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, construct strength was determined by progressive dynamic loading to failure (Fig. 2, d) 26,27 . After the application of a static preload (L PRE ), sinusoidal loading with a load amplitude of L DYN was applied at 2 Hz.…”
Section: Loadingmentioning
confidence: 99%
“…Its unique biomechanical function is based on splinting rather than compression result in flexible stabilization. Locking the screw into the plate to ensure angular as well as axial stability, eliminates the possibility for the screw to toggle, slide or be dislodged and thus strongly reduces the risk of postoperative loss of reduction and implant failure [5] . The Locking Compression Plate system combines the facilities of conventional plate osteosynthesis with those of the internal fixator systems.…”
Section: Introductionmentioning
confidence: 99%